Perianal abscess in children: A paediatric infectious disease perspective - Sevgen Tanır Basaranoglu; Yasemin Ozsurekci; Ali Bulent Cengiz; Eda Karadag Oncel; Kubra Aykac; Ates Kara; Mehmet Ceyhan (Elsevier, 2019)
Introduction: There are limited data on the aetiology and management of perianal abscesses (PAs). The aim of this retrospective study was to define the characteristics of children with PAs; describe our experience with PA from the perspective of paediatric infectious medicine and determine the factors that influence clinical outcomes. Methods: We performed a retrospective review of cases of PA in children with no underlying disease managed in a tertiary referral hospital between January 2005 and July 2015. We collected data on demographic characteristics, symptoms, abscess size and location, abscess recurrences, laboratory and microbiological findings, treatment modalities, diagnosis of systemic illness at the end of the diagnostic workup and clinical outcomes. Results: We included a total of 47 patients in the study, with a predominance of male patients (93.6 vs 6.4%, P < .001). The median age was 7.7 months (IQR 1.8-13.7 months), and 40 children (85.1%) were younger than 2 years of age. Four PAs drained spontaneously and 7 healed without need of drainage (23.4%). Drainage by simple incision was applied to 36 patients (76.5%) and six PAs required fistulotomy (12.7%). Recurrent abscesses were found in 25 patients (53.1%). Three patients with recurrent PA were diagnosed with inflammatory bowel disease at the end of the diagnostic evaluation. Conclusions: Based on the findings of our study, measurement of white blood cell counts and serum levels of acute phase reactants may be useful in the initial evaluation of children with PA. In light of the high relapse rates observed in surgically managed patients, it seems reasonable to use a conservative approach in patients aged less than 2 years. Resumen: Introducción: Existen datos limitados acerca de los abscesos perianales (AP), con respecto a su etiología y tratamiento. Este estudio retrospectivo tiene como objetivo definir las características de los niños con AP, detallar nuestra experiencia en el campo de las enfermedades infecciosas pediátricas y determinar los factores que influyen en los resultados clínicos. Métodos: Entre enero de 2005 y julio de 2015 se llevó a cabo una revisión retrospectiva de niños con AP sin enfermedad subyacente en un hospital de referencia de nivel terciario. La información incluyó características demográficas, síntomas, tamaño y localización del absceso, recurrencias de los abscesos, hallazgos de laboratorio y microbiológicos, modalidades de tratamiento, diagnóstico de enfermedades sistémicas al finalizar las investigaciones etiológicas y pronóstico. Resultados: En el estudio se incluyeron 47 pacientes, con predominio masculino (93,6 frente a 6,4%, p < 0,001). La mediana de edad fue de 7,7 meses (rango intercuartílico 1,8 a 13,7 meses) y 40 de los niños (85,1%) tenían menos de 2 años de edad. Cuatro AP drenaron espontáneamente y 7 curaron sin necesidad de drenaje (23,4%). Se aplicó drenaje mediante incisión simple a 36 pacientes (76,5%) y 6 AP requirieron de fistulotomía (12,7%). Se observaron abscesos recurrentes en 25 pacientes (53,1%). Tres pacientes con AP recurrentes fueron diagnosticados de enfermedad inflamatoria intestinal al finalizar las investigaciones. Conclusiones: De acuerdo con los hallazgos del presente estudio, la determinación de la cifra de leucocitos, así como de los reactantes de fase aguda, parece ser útil en la primera evaluación de los niños con AP. En cuanto a las altas tasas de recurrencia en pacientes sometidos a procedimientos quirúrgicos, resulta razonable el uso de enfoques conservadores para pacientes menores de 2 años.